Processing technology of red halloysite and calcined red halloysite prepared by processing technology
By adsorbing and washing the erythrite powder with pretreatment liquids such as carboxymethyl chitosan-methacryloyloxyethyltrimethylammonium chloride graft copolymer, combined with the calcination process, the calcination in the prior art was solved The problem of high lead content in red lime has achieved the effect of effectively reducing the content of harmful metals at lower temperatures.
Patent Information
- Application Number
- CN202411211826.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When the existing red lime fat preparation process reduces the harmful metal lead content in calcined red lime fat, it is necessary to increase the fuming temperature to about 800℃, which consumes a lot of energy and is difficult to effectively remove lead.
The erythrite powder was pretreated with a mixed solution of carboxymethyl chitosan-methacryloyloxyethyltrimethylammonium chloride graft copolymer, acetic acid and water, and the lead was adsorbed and removed, and then washed by water. and the calcination process further reduces the harmful metal content.
It effectively reduces the content of lead and mercury in calcined erythrite, reduces the fuming temperature to 545-555℃, saves energy consumption, and improves the efficiency of lead removal.
Smart Images

Figure BDA0005020500990000061
Abstract
Description
Technical Field
[0001] The present application relates to the field of processing of traditional Chinese medicine, and in particular to a processing technology of red ochre and the calcined red ochre obtained therefrom. Background Art
[0002] Red ochre has the effects of astringing the intestines, stopping bleeding, promoting tissue regeneration and healing sores. In clinical practice, calcined red ochre raw powder is mostly used as medicine.
[0003] The current pharmacopoeia standard for the preparation of red ochre is: crush the red ochre after removing impurities, then take the red ochre fine powder, mix it with vinegar, then roll it into strips, cut it into sections, dry it, and pound it according to the Ming pounding method (General Rule 0213) until it turns red, and crush it when used.
[0004] Among them, red ochre is usually used as medicine in its raw powder, and reducing the content of harmful heavy metals (such as lead and mercury) in calcined red ochre is of great significance. However, according to the research of relevant technologies, mercury itself is a volatile metal element and is relatively easy to remove. However, if the content of harmful metal lead in calcined red ochre is to be effectively reduced, the calcination temperature of red ochre usually needs to be increased to about 800℃, which consumes a lot of energy. Summary of the invention
[0005] In order to effectively reduce the harmful metal content in calcined red ochre while lowering the calcination temperature of the red ochre, the present application provides a processing process for red ochre and the calcined red ochre obtained.
[0006] In the first aspect, the present application provides a processing process for red ochre using the following technical solution: A processing process of red ochre comprises the following steps: S1, removing impurities attached to the surface of red ochre to obtain purified red ochre; S2, crushing and sieving the purified red ochre to obtain red ochre powder; S3, soaking the red ochre powder in a pretreatment liquid, then separating the red ochre powder from the pretreatment liquid, and washing the separated red ochre powder with water to obtain pretreated red ochre powder; wherein the pretreatment liquid is a mixed solution of carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer, acetic acid and water; S4, taking the pretreated red ochre powder and adding it to vinegar, mixing and blending, and then rolling and cutting into sections to obtain red ochre strips; S5, drying the red ochre strips until the moisture content is qualified, then calcining the dried red ochre strips at 545-555° C. until they are red, and cooling to obtain calcined red ochre.
[0007] The difference between the present application and the existing red ochre processing process is that after the red ochre powder is obtained by crushing the red ochre, the present application first uses a pretreatment liquid to soak the red ochre powder, and the pretreatment liquid is a mixed solution of carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer, acetic acid and water. The pretreatment liquid can adsorb part of the harmful metal element lead attached to the red ochre powder, so that most of the lead is transferred from the red ochre powder to the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer, and then the red ochre powder after soaking is washed with water to remove the pretreatment liquid remaining on the surface, which can further reduce the lead residue on the pretreated red ochre powder, which is beneficial to further reduce the content of harmful metal element lead in calcined red ochre.
[0008] Among them, the present application first pre-treats the red ochre powder and then mixes, rolls, cuts and calcines it. The pre-treatment process can remove most of the heavy metal lead in the red ochre, and during the calcination process, mercury and a small amount of remaining lead turn into mercury vapor and lead vapor and escape as the temperature rises. Due to the addition of the pre-treatment process, the burden of calcination and lead removal in the related technology is effectively reduced, so that the harmful metal lead and mercury in the calcined red ochre can be effectively reduced when the calcination temperature is 545-555°C.
[0009] In some specific embodiments, the weight ratio of the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer, acetic acid and water is (4.5-7.8): (15-20): (80-85).
[0010] In the present application, the pretreatment liquid adopts carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer, acetic acid and water in a weight ratio of (4.5-7.8): (15-20): (80-85), which is beneficial to transfer the harmful metal element lead in the red ochre powder to the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer, thereby effectively reducing the content of harmful metal lead in the pretreated red ochre powder.
[0011] In some specific embodiments, the weight ratio of the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer, acetic acid and water is (5.5-6.5): (15-20): (80-85).
[0012] In the present application, the pretreatment liquid is further preferably a composition of carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer, acetic acid and water in a weight ratio of (5.5-6.5): (15-20): (80-85), which is beneficial for transferring the harmful metal element lead in the red ochre powder to the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer, and can also reduce the difficulty of cleaning the red ochre powder after immersion treatment, and prevent the residue of carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer.
[0013] In some specific embodiments, in the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride grafted copolymer, the average number of moles of methacryloyloxyethyl trimethyl ammonium chloride grafted onto each mole of carboxymethyl chitosan repeating unit is 0.55-0.65 mol.
[0014] In the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer used in the pretreatment liquid of the present application, the average number of moles of methacryloyloxyethyl trimethyl ammonium chloride grafted on each mole of carboxymethyl chitosan repeating unit is controlled within the range of 0.55-0.65 mol, which is beneficial to transfer the harmful metal element lead in the red ochre powder to the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer.
[0015] In some specific embodiments, in S2, the weight ratio of the red ochre powder to the pretreatment liquid is (15-20):100.
[0016] In the present application, the weight ratio of red ochre powder to pretreatment liquid is controlled to be (15-20):100, which is beneficial to transfer the harmful metal element lead in the red ochre powder to the carboxymethyl chitosan-methacryloyloxyethyl trimethylammonium chloride graft copolymer.
[0017] In some specific embodiments, in S2, the red ochre powder includes 8-12wt% of red ochre powder with a particle size range of 95-118μm, 80-90wt% of red ochre powder with a particle size range of 130-150μm, and 2-8wt% of red ochre powder with a particle size range of 155-172μm.
[0018] In the present application, by combining the above three types of red ochre powder in the particle size range, it is beneficial to obtain red ochre bars with a microporous structure, which facilitates the rapid entry of heat into the interior of the red ochre bars during the subsequent calcination process, and is beneficial to the volatilization of trace harmful metal elements such as lead and mercury in the red ochre, thereby further reducing the content of harmful metals in calcined red ochre.
[0019] In some specific embodiments, in S4, the weight ratio of the pretreated red ochre powder to vinegar is 100:(20-30).
[0020] In some specific embodiments, in S4, the length of the red ochre strip is 10-15 mm.
[0021] In the present application, the length of the red ochre strip is controlled to be 10-15 mm, which is beneficial for sufficient heating of all parts of the red ochre strip.
[0022] In some specific embodiments, in S5, the calcination time of the red ochre strips is 2-3 hours.
[0023] In the present application, the calcination time of the red ochre strips is controlled within 2-3 hours, which is beneficial to effectively reduce the harmful metal content in the red ochre strips and save energy.
[0024] In the second aspect, the calcined red ochre provided in the present application is prepared by any one of the processing processes of the red ochre mentioned above.
[0025] In summary, the technical solution of this application includes at least the following beneficial technical effects: (1) The present application first pre-treats the red ochre powder with a mixed solution of carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer, acetic acid and water, and then performs mixing, rolling, cutting and calcining. The pre-treatment process can remove most of the heavy metal lead in the red ochre, and during the calcination process, mercury and a small amount of remaining lead are converted into mercury vapor and lead vapor and escape as the temperature rises. Due to the addition of the pre-treatment process, the burden of calcination and lead removal in the related technology is effectively reduced, so that the harmful metal lead and mercury in the calcined red ochre can be effectively reduced when the calcination temperature is 545-555°C.
[0026] (2) In the present application, the pretreatment liquid is further preferably a composition of carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer, acetic acid and water in a weight ratio of (5.5-6.5): (15-20): (80-85), which is beneficial for transferring the harmful metal element lead in the red ochre powder to the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer, and can also reduce the difficulty of cleaning the red ochre powder after immersion treatment, and prevent the residue of carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer.
[0027] (3) In the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer used in the pretreatment liquid of the present application, the average number of moles of methacryloyloxyethyl trimethyl ammonium chloride grafted on each mol of carboxymethyl chitosan repeating unit is controlled in the range of 0.55-0.65 mol, which is beneficial to transfer the harmful metal element lead in the red ochre powder to the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer. DETAILED DESCRIPTION
[0028] The present application is further described below in conjunction with specific experiments. Example
[0029] [Example 1] A calcined red ochre, the processing process of which comprises the following steps: S1, removing impurities attached to the surface of red ochre to obtain purified red ochre; S2, crushing and sieving the purified red ochre to obtain red ochre powder; wherein the red ochre powder includes 8wt% of red ochre powder with a particle size range of 95-118μm, 90wt% of red ochre powder with a particle size range of 130-150μm, and 2kg of red ochre powder with a particle size range of 155-172μm; S3, soaking the red ochre powder in a pretreatment liquid, then separating the red ochre powder from the pretreatment liquid, and washing the separated red ochre powder with water to obtain pretreated red ochre powder; wherein the weight ratio of the red ochre powder to the pretreatment liquid is 20:100, and the pretreatment liquid adopts a mixed solution of 4.5kg of carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer with a molecular weight of 100,000-120,000, 15kg of acetic acid and 85kg of water, and the number of moles of methacryloyloxyethyl trimethyl ammonium chloride grafted on each mol of carboxymethyl chitosan repeating unit in the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer is 0.55mol; S4, taking the pre-treated red ochre powder and adding it to vinegar, mixing and blending, then rolling and cutting into sections to obtain red ochre strips with a length of 10-15 mm; wherein the weight ratio of the pre-treated red ochre powder to the vinegar is 100:20; S5. Dry the red ochre strips until the moisture content is qualified, then place the dried red ochre strips in an environment of 545°C for 3 hours, calcine them until they are red, and cool them to obtain calcined red ochre.
[0030] [Example 2] A calcined red ochre, the processing process of which comprises the following steps: S1, removing impurities attached to the surface of red ochre to obtain purified red ochre; S2, crushing and sieving the purified red ochre to obtain red ochre powder; wherein the red ochre powder includes 12wt% of red ochre powder with a particle size range of 95-118μm, 80wt% of red ochre powder with a particle size range of 130-150μm, and 8kg of red ochre powder with a particle size range of 155-172μm; S3, soaking the red ochre powder in a pretreatment liquid, then separating the red ochre powder from the pretreatment liquid, and washing the separated red ochre powder with water to obtain pretreated red ochre powder; wherein the weight ratio of the red ochre powder to the pretreatment liquid is 15:100, and the pretreatment liquid adopts a mixed solution of 7.8kg of carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer with a molecular weight of 100,000-120,000, 20kg of acetic acid and 80kg of water, and the number of moles of methacryloyloxyethyl trimethyl ammonium chloride grafted on each mol of carboxymethyl chitosan repeating unit in the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer is 0.65mol; S4, taking the pre-treated red ochre powder and adding it to vinegar, mixing and blending, then rolling and cutting into sections to obtain red ochre strips with a length of 10-15 mm; wherein the weight ratio of the pre-treated red ochre powder to the vinegar is 100:30; S5. Dry the red ochre strips until the moisture content is qualified, then place the dried red ochre strips in an environment of 555°C for 2 hours, calcine them until they are red, and cool them to obtain calcined red ochre.
[0031] [Example 3] A calcined red ochre, which differs from [Example 1] in that: in the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride grafted copolymer, the average number of moles of methacryloyloxyethyl trimethyl ammonium chloride grafted on each mole of carboxymethyl chitosan repeating unit is 0.25 mol.
[0032] [Example 4] A calcined red ochre, which differs from [Example 1] in that: in step S2, the red ochre powder includes 30wt% of red ochre powder with a particle size range of 95-118μm, 50wt% of red ochre powder with a particle size range of 130-150μm, and 20kg of red ochre powder with a particle size range of 155-172μm.
[0033] [Example 5] A calcined red ochre, which differs from [Example 1] in that: in step S2, the red ochre powder includes 40wt% of pretreated red ochre powder with a particle size range of 95-118μm and 60wt% of red ochre powder with a particle size range of 130-150μm.
[0034] Comparative Example [Comparative Example 1] A calcined red ochre, which differs from [Example 1] in that the step of pretreating the red ochre powder in S3 is omitted.
[0035] [Comparative Example 2] A calcined red ochre, which differs from [Example 1] in that the acetic acid in the pretreatment solution in step S3 is replaced by an equal amount of water.
[0036] [Comparative Example 3] A calcined red ochre, which differs from [Example 1] in that the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer in the pretreatment solution of step S3 is replaced by an equal amount of carboxymethyl chitosan.
[0037] [Comparative Example 4] A calcined red ochre, which is different from [Comparative Example 1] in that the calcination temperature of the red ochre strips is 800°C.
[0038] Performance testing Preparation of the test sample: Take 0.5 g each of the red ochre powder in S2, the pretreated red ochre powder in S3, and the calcined red ochre obtained in step S5, moisten them with deionized water, add 6 mL of hydrochloric acid and 2 mL of nitric acid, and then heat to dissolve. After cooling, add 5 mL of hydrochloric acid, boil, cool again, then transfer to a 100 mL volumetric flask, and finally add deionized water to dilute to the scale to obtain the test sample.
[0039] 1. Determination of lead content: refer to graphite furnace atomic absorption spectrometry, test conditions: wavelength 283.3nm, drying temperature 110℃, lasting 25s; ashing temperature 600℃, lasting 25s; atomization temperature 1200℃, lasting 4s. Randomly select 10 small samples from the samples corresponding to each embodiment and comparative example to prepare the test samples, and after the test is completed, record the average lead content of each sample.
[0040] 2. Determination of mercury content: refer to the atomic fluorescence spectrometer method, the determination conditions are: carrier gas is nitrogen, carrier gas flow rate is 300mL / min, auxiliary gas flow rate is 400mL / min; atomization mode is cold atom, atomizer temperature is 200F, reading time is 32s, delay time is 5s; injection volume: 5mL; 0.05% potassium borohydride and 0.3% sodium hydroxide mixed solution (prepared before use) is used as a reducing agent, and hydrochloric acid solution (5100) is used as a carrier liquid. Randomly select 10 small samples from the samples corresponding to each embodiment and comparative example to prepare the test samples. After the test is completed, record the average mercury content of each sample.
[0041] Table 1 By comparing Example 1 with Comparative Example 1 and combining the test data in Table 1, it can be seen that after omitting the step of pretreating the red ochre in S3, the average lead content in the calcined red ochre product is significantly increased, indicating that the pretreatment step added in S3 can effectively reduce the lead content in the calcined red ochre.
[0042] By comparing Example 1 with Comparative Example 2 and combining with the test data in Table 1, it can be seen that after the acetic acid in the pretreatment liquid in step S3 is replaced by an equal amount of water, the average lead content in the pretreated red ochre powder is not much different from the average lead content in the red ochre powder, and the average lead content in the calcined red ochre product is also significantly increased relative to Example 1, indicating that the addition of acetic acid is beneficial to the removal of lead in the red ochre powder, can reduce the energy consumption burden in the subsequent red ochre calcination process, and can achieve effective removal of lead at a lower temperature.
[0043] By comparing Example 1 with Comparative Example 3 and combining with the test data in Table 1, it can be seen that after the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer in the pretreatment liquid in step S3 is replaced by an equal amount of carboxymethyl chitosan, the ability of the pretreatment liquid to remove lead from red ochre powder decreases, and the average lead content in the calcined red ochre product is also increased relative to Example 1, indicating that the use of carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer is more conducive to the removal of lead from red ochre powder, can reduce the energy consumption burden in the subsequent red ochre calcination process, and can achieve effective removal of lead at a lower temperature.
[0044] By comparing Example 1 with Example 3 and combining with the test data in Table 1, it can be seen that in the carboxymethyl chitosan-methacryloyloxyethyltrimethylammonium chloride grafted copolymer, when the average number of moles of methacryloyloxyethyltrimethylammonium chloride grafted on each mole of carboxymethyl chitosan repeating unit is low, the ability of the pretreatment liquid to remove lead decreases, and the average lead content in the calcined red ochre product increases.
[0045] By comparing Example 1 with Examples 4-5 and combining with the detection data in Table 1, it can be seen that in step S2, when the red ochre powder includes 8-12wt% of red ochre powder with a particle size range of 95-118μm, 80-90wt% of red ochre powder with a particle size range of 130-150μm and 2-8wt% of red ochre powder with a particle size range of 155-172μm, it is more conducive to obtaining red ochre strips with a microporous structure, which facilitates the rapid entry of heat into the interior of the red ochre strips during the subsequent calcination process, which is beneficial to the volatilization of trace harmful metal elements lead and mercury in the red ochre, thereby further reducing the content of harmful metals in the calcined red ochre.
[0046] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A processing technology of red ochre, It is characterized in that The following steps are involved: S1, removing impurities attached to the surface of red ochre to obtain purified red ochre; S2, crushing and sieving the purified red ochre to obtain red ochre powder; S3, soaking the red ochre powder in a pretreatment liquid, then separating the red ochre powder from the pretreatment liquid, and washing the separated red ochre powder with water to obtain pretreated red ochre powder; wherein the pretreatment liquid is a mixed solution of carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer, acetic acid and water; S4, taking the pretreated red ochre powder and adding it to vinegar, mixing and blending, and then rolling and cutting into sections to obtain red ochre strips; S5, drying the red ochre strips until the moisture content is qualified, then calcining the dried red ochre strips at 545-555° C. until they are red, and cooling to obtain calcined red ochre.
2. The processing technology of red ochre according to claim 1, Features: The weight ratio of the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer, acetic acid and water is (4.5-7.8): (15-20): (80-85).
3. The processing technology of red ochre according to claim 2, Features: The weight ratio of the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer, acetic acid and water is (5.5-6.5): (15-20): (80-85).
4. A processing process of red ochre according to any one of claims 1 to 3, Features: In the carboxymethyl chitosan-methacryloyloxyethyl trimethyl ammonium chloride graft copolymer, the average number of moles of methacryloyloxyethyl trimethyl ammonium chloride grafted onto each mole of carboxymethyl chitosan repeating unit is 0.55-0.65 mol.
5. A processing process of red ochre according to any one of claims 1 to 3, Features: In S2, the weight ratio of the red ochre powder to the pretreatment liquid is (15-20):
100.
6. A processing process of red ochre according to any one of claims 1 to 3, Features: In S2, the red ochre powder includes 8-12wt% of red ochre powder with a particle size range of 95-118μm, 80-90wt% of red ochre powder with a particle size range of 130-150μm, and 2-8wt% of red ochre powder with a particle size range of 155-172μm.
7. A processing process of red ochre according to any one of claims 1 to 3, Features: In S4, the weight ratio of the pretreated red ochre powder to vinegar is 100:(20-30).
8. A processing process of red ochre according to any one of claims 1 to 3, Features: In S4, the length of the red ochre strip is 10-15 mm.
9. A processing process of red ochre according to any one of claims 1 to 3, Features: In S5, the calcination time of the red ochre strips is 2-3 hours.
10. A kind of calcined red ochre, Features: It is prepared by the processing process of red ochre according to any one of claims 1 to 9.
Citation Information
Patent Citations
Sanjisihuan Pill for treating internal and external hemorrhoids by oral administration and anal application
CN103784655A
Modified carboxymethyl chitosan quaternary ammonium salt and preparation method thereof
CN114539444A
